{4-Hydroxy-N'-[(2E, 3Z)-4-oxido-4-phenylbut-3-en-2-ylidene] benzohydrazidato} diphenyltin (IV) methanol monosolvate - Fasihuddin B, Ahmad; Md Abu, Affan; Norrihan B Sam, Sam; Fraser, White; Edward RT, Tiekink (International Union of Crystallography, 2011)
Two independent diphenyltin molecules and two independent methanol molecules comprise the asymmetric unit of the title compound, [Sn(C6H5)2(C17H14N2O3)]·CH3OH. The Sn atom in each is five-coordinated by a tridentate ligand and the ipso-C atoms of the Sn-bound benzene substituents. The resulting C2N2O donor set defines a coordination geometry that is intermediate between trigonal-bipyramidal (TP) and square-pyramidal (SP), with one molecule slightly tending towards TP and the other slightly towards SP. The molecules differ in terms of the relative orientations of the terminal benzene rings [dihedral angles = 45.71 (18) and 53.98 (17)°] and of the Sn-bound benzene substituents [dihedral angles = 59.5 (2) and 45.77 (18)°, respectively]. The most prominent feature of the crystal packing is the formation of four-molecule aggregates via O-H...O and O-H...N hydrogen bonds, in which the hydroxy group is connected to a methanol molecule which, in turn, is linked to a non-coordinating N atom. Weak C-H...[pi] interactions also occur.